Pengaruh Self Efficacy Terhadap Jenis Persalinan pada Ibu Bersalin di RSUD Sultan Suriansyah Banjarmasin - Muslimah; Sismeri Dona; Meldawati (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Self Efficacy is the expectation of how far a person is able to perform a behavior in a given situation. Strong Self efficacy is very beneficial for maternity mothers so that it can affect the smooth delivery process. Normal and abnormal childbirth both have a great influence on the birth of a baby. Analyze the effect of self-efficacy on the type of childbirth in maternity mothers at Sultan Suriansyah Hospital Banjarmasin. Quantitative research using cross sectional approach. The population and sample of the study were 40 maternity mothers with purposive sampling techniques. The measuring instrument used is a questionnaire whose results are analyzed using the Chi Square Test. Respondents with low self-efficacy had more abnormal labors, which were 9 people (22.5%). Similarly, in respondents with high self-efficacy, 16 people (40%) experienced abnormal labor. The results of the chi square test show a p value of 0.477. There is no effect of self-efficacy on the type of childbirth in maternity mothers at RSUD Sultan Suriansyah Banjarmasin.